2014
DOI: 10.1016/j.pharep.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of antidepressants alone and after their local co-administration with morphine in a rat model of neuropathic pain

Abstract: (2014) 'Analgesic eects of antidepressants alone and after their local co-administration with morphine in a rat model of neuropathic pain.', Pharmacological reports., 66 (3). pp. 459-465. Further information on publisher's website: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…The first phase of the investigation shows firstly that the co-occurrence of both conditions involves a higher level of generalized hypersensitivity to pain at somatic level with respect to migraine only and fibromyalgia only, as testified by significantly lower pain thresholds in both painful and control areas. All FMS, but not non-FMS, patients were under stable basal amitriptyline treatment; though in very low doses, this treatment could have potentially influenced pain sensitivity in FMS, by increasing the pain threshold [ 35 , 42 ]. However, even in this case, the outcome here found of a higher pain sensitivity in FMS vs non-FMS would not have changed without treatment; in contrast, the hypersensitivity difference would probably have been more pronounced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first phase of the investigation shows firstly that the co-occurrence of both conditions involves a higher level of generalized hypersensitivity to pain at somatic level with respect to migraine only and fibromyalgia only, as testified by significantly lower pain thresholds in both painful and control areas. All FMS, but not non-FMS, patients were under stable basal amitriptyline treatment; though in very low doses, this treatment could have potentially influenced pain sensitivity in FMS, by increasing the pain threshold [ 35 , 42 ]. However, even in this case, the outcome here found of a higher pain sensitivity in FMS vs non-FMS would not have changed without treatment; in contrast, the hypersensitivity difference would probably have been more pronounced.…”
Section: Resultsmentioning
confidence: 99%
“…Further antidepressants were excluded since all patients were already under amitriptyline treatment. Among calcium-channel blockers, flunarizine was chosen as, according to guidelines, it represents the molecule with the highest level of evidence of efficacy [ 35 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…assays of acid-stimulated stretching in rats and mice (Cowan et al, 1977;Fürst, 1991;Stevenson et al, 2006;Pereira Do Carmo et al, 2009). Previous studies have also shown that m-opioid agonists block other examples of pain-stimulated behavior, such as tail-or paw-withdrawal responses from noxious thermal stimuli Holtzman, 1991, 1992;Gringauz et al, 2001;Taracha et al, 2009) or withdrawal responses in subjects rendered hypersensitive to thermal or mechanical stimuli by inflammatory or neuropathic manipulations (Wang et al, 2006;Cobos et al, 2012;Jagla et al, 2014). m-Agonist effects on pain-stimulated behaviors are often interpreted as evidence consistent with clinical analgesic efficacy .…”
Section: Discussionmentioning
confidence: 99%
“…This signifies that amitriptyline showed analgesic activity mainly through central analgesic mechanism which is similar to the results found in previous studies. [24][25][26][27] In authors study we also found that amitriptyline showing analgesic activity through peripheral mechanism as evidenced by decrease in number of writhes in mice, although this decrement was not as good as diclofenac. But authors can't completely disagree with this fact that it partially improved pain through peripheral mechanism also.…”
Section: Resultsmentioning
confidence: 99%